Hubungan antara intensitas aktivitas fisik, kualitas tidur dan tingkat stres pada kebugaran fisik remaja - Kasmadi, Muchammad; Suhadi, Suhadi (Universitas Nusantara PGRI Kediri, 2024)
Physical activity, sleep quality, and stress levels on physical fitness in adolescence can increase the positive value of adolescent students' development in doing all activities. At the same time, previous research has shown that physical activity, stress levels and sleep quality strongly influence each of these activities in the context of positive influences. Because adolescent activity is so high, the study examined this relationship in everyday life. The design and method used in this study were correlational, with 200 adolescent students involved in this study who selected purposive sampling. Data collection techniques are questionnaires, among which IPAQ is a questionnaire with a physical activity measurement scale. Sleep quality using PSQI (Pittsburgh Sleep Quality Index). Stress rating scale using DASS (Depression Anxiety Stress Scales). Physical fitness is measured using the Indonesian Physical Fitness Test for 16-19 years. Data analysis using Spearman's rho correlation test using SPSS application version 26. This study found that in physical activity with adolescent physical fitness, Sig. 0.714 > 0.05 was obtained, which shows a significant relationship between physical activity and physical fitness. Sleep quality with physical fitness in adolescents obtained Sig. Value 0.826 > 0.05, so there is a significant relationship between sleep quality and physical fitness in adolescents. At the level of stress related to physical fitness, they obtained Sig. Values of 0.000 < 0.05 mean that no significant relationship exists between adolescents' stress levels and physical fitness.